1987
DOI: 10.1038/bjc.1987.222
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum lipids related to the presence of experimental colon cancer

Abstract: Summary People at risk from coronary heart disease and large bowel cancer are drawn from the same urbanised, industrialised Western populations. Whilst changes in blood lipids are well recognised in heart disease, little is known of their role in large bowel cancer. This study investigates serial alterations in blood lipids in the 1,2-dimethylhydrazine (DMH) rat model of colon cancer. Eighty Wistar rats received a 5 weekly regimen of DMH. At week 10, and at 5 weekly intervals until week 40, random groups of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This suggests overlapping mechanisms that increase the risk of colon cancer and hyperlipidemia. On the contrary, other reports failed to detect a significant association between serum levels of triglyceride as well as cholesterol and risk of colorectal cancer in human [16,17] and animal studies [18] . Thus, the true association between circulating lipid levels and colonic neoplasm development has not been satisfactorily determined in humans.…”
Section: Introductionmentioning
confidence: 67%
“…This suggests overlapping mechanisms that increase the risk of colon cancer and hyperlipidemia. On the contrary, other reports failed to detect a significant association between serum levels of triglyceride as well as cholesterol and risk of colorectal cancer in human [16,17] and animal studies [18] . Thus, the true association between circulating lipid levels and colonic neoplasm development has not been satisfactorily determined in humans.…”
Section: Introductionmentioning
confidence: 67%
“…At present, it still cannot be stated with certainty whether hyperlipidemia is a leading cause of intestinal polyp formation. Colon tumors induced by 1,2-dimethylhydrazine in rats, however, are not linked to serum lipid levels (19). As hyperlipidemia and polyp formation could be related to Apc-deficiency independently, we now address whether low LPL activity and high serum lipid levels could promote intestinal polyp formation in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study showed a significant increase in the levels of serum lipid profile other than HDL demonstrating a hyperlipidaemic state that is associated with massive tumour burden in DMH alone administered rats. In contrast it has been reported that there are no notable changes in serum triglycerides and total cholesterol in rats with colon tumours induced by 1,2-dimethylhydrazine though there was an increased tumour burden (Barton, Cruse, & Lewin, 1987). Hence it can be speculated that high dietary fat played a remarkable role in eliciting hyperlipidaemia in the DMH model.…”
Section: Discussionmentioning
confidence: 90%